2006
DOI: 10.1002/biot.200600001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of human indoleamine 2,3‐dioxygenase identified with a target‐based screen in yeast

Abstract: Indoleamine 2,3-dioxygenase (IDO) is a tryptophan degradation enzyme that is emerging as an important drug target. IDO is expressed by many human tumors to help them escape immune detection, and it has been implicated in depression and in the formation of senile nuclear cataracts. There is a need for potent and selective IDO inhibitors for use in research and as lead compounds for drug development. We show that expression of human IDO in a Saccharomyces cerevisiae tryptophan auxotroph restricts yeast growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 28 publications
3
47
1
1
Order By: Relevance
“…We generated a humanized yeast strain-BLOCKADE-where both pathways that lead to NAD + production were abolished by co-deletion of BNA2 and NPT1 genes, making cell survival dependent on the activity of human IDO. Although previous studies suggested that expression of human IDO in yeast was able to promote tryptophan degradation, 21 our work showed for the first time that IDO activity is able to functionally complement disruption of the kynurenine pathway caused by BNA2 deletion. Growth of the BLOCKADE strain was responsive to the level of IDO activity, providing a readout for a life/death assay for the identification of IDO inhibitors.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We generated a humanized yeast strain-BLOCKADE-where both pathways that lead to NAD + production were abolished by co-deletion of BNA2 and NPT1 genes, making cell survival dependent on the activity of human IDO. Although previous studies suggested that expression of human IDO in yeast was able to promote tryptophan degradation, 21 our work showed for the first time that IDO activity is able to functionally complement disruption of the kynurenine pathway caused by BNA2 deletion. Growth of the BLOCKADE strain was responsive to the level of IDO activity, providing a readout for a life/death assay for the identification of IDO inhibitors.…”
Section: Discussioncontrasting
confidence: 66%
“…24,25 Therefore, most yeast assays are performed using modified strains where pumps are deleted. 21,26 On the contrary, the BLOCKADE strain kept all the transporter systems intact, as we proposed to detect only compounds with high specificity. We deliberately expected to lose some potential hits, to ensure we were selecting the most potent compounds.…”
Section: Discussionmentioning
confidence: 99%
“…to treat autoimmune diseases [10] or transplant rejection [66][67][68] or to augment antitumour immune responses [69][70][71][72][73]. In this light, the development of synthetic TCs [10] or pharmacologic inhibitors of IDO [74][75][76][77][78][79] represent promising immu- HAO beef liver [216] rat brain [217] rat liver [217] immortalized murine macrophages MT2 [215] immortalized murine microglial cells N11…”
Section: Trp Degradation As a Therapeutic Mechanism In Autoimmune Infmentioning
confidence: 99%
“…[13,17] An investigation concerning the inhibitory properties of 4-phenylimidazole (4-PI) [25] has witnessed the crystal structure of IDO-1 being determined, [28] along with the production of nanomolar inhibitors of IDO-1 based on the 4-PI scaffold. [29] Numerous synthetic IDO-1 inhibitors with novel pharmacophores have emerged, including several based on the indole heterocycle, [30][31][32][33] S-benzyl isothioureas, [34] 4-amino-1,2,5-oxadiazole-3-carboximidamides, [35,36] the imidodicarbonimidic diamide NSC 401366, [37] ebselen, [38] and several triazole-based IDO inhibitors. [39] Potent inhibitors have also been discovered using a combination of docking-based pharmacophore model development and fragment-based drug design (FBDD), [40a] along with the identification of potential inhibitors by virtual screening [40b] (Fig.…”
Section: Introductionmentioning
confidence: 99%